Las redes sociales y su influencia en el aprendizaje colaborativo de los alumnos del segundo de bachillerato de electromecánica de la Unidad Educativa Jaime Roldós Aguilera periodo lectivo 2021-2022 - Melendez Yanez, Ana Yulexy (2022)
This case study is aimed at analyzing the use of social networks and collaborative learning of students in the second year of electromechanics. At the same time, this study was compiled through the quantitative approach since it allows conclusions to be drawn, it is there that the deductive methods are applied, it allowed reasoning of the results and the analytical-synthetic ones, these contribute to studying the main object of the theme carried out and then carry out the survey technique and as an instrument a questionnaire in Google Form, which was applied to the population with around 25 students enrolled in the Jaime Roldós Aguilera Educational Unit. In this way, the positive influences that the students present with the use of social networks in the classroom and that contribute to knowledge when carrying out academic activities were obtained as results, managing to develop collaborative learning, where they presented influences negative since the speakers are diverted in the search for information and the limitation of communication with the teacher. The implementation of social networks in education creates positive/negative influences. Also, they achieve collaborative learning in a way that allows spaces to exchange information, communicate, etc. At the same time, the proper use of social networks in students contributes to teamwork and reaches open conversations that arise through social networks carried out by the teacher as a guide for students to develop the ability to interact and communicate. instantly.